Symptom severity grades of cotton leaf curl disease and its effect on the yield and fibre quality of upland cotton in Punjab, India - SINGH, DALJEET (Indian Phytopathology, 2006)
Cotton is one of the most important cash crops in India . The productivity of cotton in the last five years has suffered a great set back due to cotton leaf curl disease (CLCuD) in Indian Punjab. The causal agent of CLCuD is a begmovirus complex and is transmitted by whitefly (Bemisia tabaci Genn.). Considering the importance of CLCuD in terms of seed cotton yield losses and quality characters, the present studies were conducted with an objective to estimate the losses in seed cotton yield and fibre characters of upland cotton. For this purpose the experiment was conducted for four years from kharif 2001 to kharif 2004 seasons at Punjab Agricultural University, Regional Station, Faridkot. Results of pooled data of four years indicated that on an average, there was 50.4% reduction in number of bolls due to CLCuD infection, reduction of 42.9% in the boll weight. Due to CLCuD the fibre length was reduced by 5.2%, strength by 5.4%, elongation by 10.0%, uniformity by 2.2% and miconaire value by 4.1% in diseased plants over (healthy plants). Therefore on the basis of four years studies it was concluded that CLCuD infection adversely affected seed cotton yield and quality characters of upland cotton fibre, which ultimately affected its market value within and outside the country.